Analysis of hydroxy fatty acids using GC-EI-MS and HPLC-ESI-MS - Grahammer, Johannes (Jihočeská univerzita, 2021)
The analysis of three different Hydroxyeicosatetraenoic acid in human blood plasma shall be determined using gas chromatography with electron ionization and high pressure liquid chromatogtaphy with electron spray ionization. The results shall be compared in terms of sensitivity, linearity and simplicity. Additionally the extraction of the lipids via protein precipitation shall be optimized.
Analysis of hydroxy fatty acids using GC-EI-MS and HPLC-ESI-MS
-
Keywords: GC-EI-MS; HPLC-ESI-MS; Derivatization; Lipid Extraction; Hydroxyeicosatetraenoic acid; Plasma; GC-EI-MS; HPLC-ESI-MS; Derivatization; Lipid Extraction; Hydroxyeicosatetraenoic acid; Plasma